Authoritarian, authoritative, and permissive parenting: their influence on school truancy behavior - Diana Wulandari; Aminah Norudin; Arnelia Dwi Yasa (Universitas Kanjuruhan Malang, 2026)
School truancy is a serious issue in education. This study aimed to examine the influence of parenting styles on school truancy and identify the most dominant parenting style affecting truancy behavior. The population consisted of 1,500 students with at least three truancy records in one semester, from which 500 students were selected through purposive sampling. Data were collected using the Parental Authority Questionnaire (PAQ) and analyzed using descriptive statistics and multiple linear regression. The mean scores for authoritarian, authoritative, and permissive parenting styles were 3.12, 3.10, and 3.12, respectively. Results indicated that all parenting styles significantly influenced truancy (p < 0.05). Permissive parenting showed the strongest effect (β = 0.396), followed by authoritarian (β = 0.308) and authoritative (β = 0.267). In conclusion, parenting styles significantly affect school truancy, with permissive parenting being the most influential factor.